Klausula Baku Dalam Perspektif Perjanjian Dagang - Purnomo, Singgih; Santoso, Aris Prio Agus; Habib, Muhamad; Fawzi’ah, Nurul Itsna (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
The standard clause seems to make the legal principles in the contract law seem neglected, this can be seen from the absence of negotiation in the standard clause, the bargaining position of one party so that the position of the parties is unbalanced, and the consumer is in a weak position. The purpose of this study was to determine the description of standard clauses in the perspective of trade agreements. This research method uses a normative juridical approach with secondary data collection obtained through literature and legislation relating to standard clauses and trade agreements. The data obtained from this study were then analyzed qualitatively, namely to answer the description of how standard clauses are viewed from the perspective of trade agreements. The results showed that standard clauses are allowed to be used but with limitations which do not harm other parties. In addition, Law No. 8/1999 concerning Consumer Protection also does not prohibit business actors from entering into agreements containing standard clauses for each document and/or agreement on business transactions for trading goods and/or services, as long as business actors do not make documents or agreements as set forth in Article 18 paragraph (1) and (2).